The Association Between Circulating Klotho and Dipeptidyl Peptidase-4 Activity and Inflammatory Cytokines in Elderly Patients With Alzheimer Disease - Mohsen Sedighi; Tourandokht Baluchnejadmojarad; Soudabeh Fallah; Nariman Moradi; Siamak Afshin-Majd; Mehrdad Roghani (Basic and Clinical Neuroscience, 2020)
Introduction: Klotho and dipeptidyl peptidase-4 (DPP4) are two proteins that modulate inflammatory pathways. We investigated the association between circulating klotho and DPP4 activity and their relationship with inflammatory cytokines, miR-29a, and miR-195 in Alzheimer disease (AD). Methods: This study was conducted on 16 AD patients and 16 healthy age-matched controls. Plasma levels of tumor necrosis factor-alpha (TNF-α), interleukin-1 beta (IL-1β, interleukin-6 (IL-6), klotho, and DPP4 were measured by enzyme-linked immunosorbent assay. Plasma expression of miR-29a and miR-195 were also measured and compared by a real-time polymerase chain reaction. Results: There was a significant increase in TNF-α (p=0.006), IL-1β (p=0.012), and IL-6 (p=0.012) levels in the AD subjects compared with controls. Also, we found a decrease in plasma levels of klotho and an increase in plasma levels of DPP4 in the AD group that was not significant compared with the controls. Lower expression of miR-29a (P=0.009) and higher expression of miR-195 (P=0.003) were observed in the AD group that was significant than controls. Further analysis showed a negative correlation between klotho and plasma levels of IL-6 (r=-0.58, p=0.01). Also, there was a positive correlation between plasma DPP4 activity and TNF-α levels (r=0.50, P=0.04) and IL-1β (r=0.62, P=0.01). Likewise, plasma klotho concentration showed a negative correlation with the age of AD subjects (r=-0.56, P=0.02). Conclusion: TNF-α, IL-1β, and IL-6 are involved in AD pathophysiology, and dysregulation of DPP4 and klotho may be associated with the inflammatory response of AD. Down-regulation of miR-29a and up-regulation of miR‑195 indicated the role of miRNAs in the AD process.